ENGLISH LITERATURE IN EFL CLASSES: THE CASE OF A UNIVERSITY IN VIETNAM - Vo, Lien-Huong (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Literature used to be a great source of material for language teaching when it was the heyday of the grammar-translation approach. However, its inherent linguistic complexity and the practicality of the emerging CLT approach to language teaching split language practitioners: while some turn their back on literature, others find it useful as an authentic source for language use and creativity. In the EFL context, the inclusion of English literature in language classes for language development purposes has resulted in teachers’ dilemma about the balance between teaching literature as a study and teaching it for language study purposes. This study examines how teachers of English literature at a university of foreign languages in Central Vietnam used literary works in their EFL-majoring classes and what benefits and challenges they encountered while teaching literature to EFL students in language classrooms. The study employs a qualitative research design, with relevant data being collected through structured interviews and teachers’ critical reflections. The findings showed that teachers’ approaches to literary works varied depending on literary text types and teachers’ preferences, but they tended to focus on students’ evaluation of literary beauty, their understanding of socio-cultural life, and their responses to the situation in the works. Activities to promote language proficiency were mainly oral discussion, integrated into analysis and discussion tasks. Considering the benefits of teaching English literature in an EFL setting, teachers found that they could raise students’ intercultural awareness, develop students’ critical thinking and literary competence through life-like situations in the literary works. However, the findings also gave rise to the challenges of focusing on the cultural model of teaching literature, thereby hindering the attainment of language knowledge and skills. The study implies the significance of assertive learning objectives and outcomes.